Colorado water law for non-lawyers - Jones, P. Andrew (University Press of Colorado, 2009)
Why do people fight about water rights? Who decides how much water can be used by a city or irrigator? Does the federal government get involved in state water issues? Why is water in Colorado so controversial? These questions, and others like them, are addressed in Colorado Water Law for Non-Lawyers. This concise and understandable treatment of the complex web of Colorado water laws is the first book of its kind. Legal issues related to water rights in Colorado first surfaced during the gold mining era of the 1800s and continue to be contentious today with the explosive population growth of.